PEMBERDAYAAN KELOMPOK TANI DI DESA PACCING KECAMATAN PATIMPENG KABUPATEN BONE - Ratnawati Ratnawati; Mappamiring Mappamiring; Ansyari Mone (Department of Public Administration, Muhammadiyah University of Makassar, 2017)
The objective of the research is to know how the service empowerment farmers group an the obstacle factors in the empowerment of farmers group in Paccing Village, Bone Regency. The type of the research is descriptive and qualitative which has eleven informants. The data collecting techniques used observation and interview. The data was analyzed using descriptive technique. The research result show that the empowerment of farmers group have not maximal the need of the because the lack capital and maintenance costs while price quite large, there is another factor that became the obstacles of this empowermentis minimal know ledge of farming communities both technology and treatment techniques farming.Keywords: Empowerment, farmer group ABSTRAKAdapun tujuan dilakukannya penelitian ini ialah untuk mengetahui bagaimana pemberdayaan kelompok tani dan faktor penghambat dalam pemberdayaan kelompok tani di Desa Paccing Kabupaten Bone. Jenis penelitian adalah deskriptif kualitatif dengan informan sebelas orang. Teknik pengumpulan data dikumpulkan dengan menggunakan instrumen berupa observasi, wawancara, terhadap informan. Data tersebut dianalisis secara deskriptif. Hasil penelitian ini menunjukkan bahwa pemberdayaan kelompok tani belum maksimal karena masih kurangnya modal sementara harga dan biaya perawatan bertani cukup besar. Kemudian faktor penghambat dalam pemberdayaan adalah minimnya pengetahuan masyarakat petani baik itu dalam teknologi maupun teknik perawatan dalam bertani.Kata kunci: Pemberdayaan, Kelompok Tani